Evaluation of the Utility of Capsular Stabilization Devices in a Zonular Fiber Defect Model with the Slit Side View System - Tomoyuki Kunishige; Hisaharu Suzuki; Yuji Nakano; Tsutomu Igarashi; Hiroshi Takahashi (Journal of Ophthalmology)
Capsular stabilization devices were evaluated in a zonular fiber defect model using the slit side view (SSV) system to confirm their utility for capsular stabilization during phacoemulsification. A zonular fiber defect model was made by cutting Zinn’s zonule under observation with a slit lamp microscope in a porcine eye. Phacoemulsification was performed, and the movement of the lens capsule and the depth of the anterior chamber were observed using the SSV in three groups: control group: no surgical instruments used, CE group: a capsule expander was inserted, and CTR group: a capsular tension ring was inserted. In the control group, the equator of the lens was unstable and was easily suctioned to the port of the ultrasound handpiece. The lens capsule was stable in both in the CE and CTR groups. In the CTR group, the equator responsible for the zonular rupture also returned and closed true to its original position. The utility of the capsular stabilization devices in this zonular fiber defect model was confirmed with the SSV system.